Sviluppare ambienti inclusivi nella formazione universitaria online: esiti di una ricerca esplorativa. - Fabio Bocci; Gianmarco Bonavolontà (LED Edizioni Universitarie, 2020)
This paper refers to the «Interdisciplinary Research Project» of the Department of Education at Roma Tre University. The title of the project is «E-learning for higher education: setting up an integrated model for the qualification of learning and educational relationships in online courses» and represents a development of a previous research (Bocci, 2019a), which was aimed at outlining some dimensions and issues of inclusive online education. Taking as a background the different theoretical perspectives that study inclusion and inclusive processes (such as the Bio-Psycho-Social Model, the Social Model, the Capability Approach and the Universal Design) in the present paper the authors show the results of an exploratory survey aimed at verifying the validity of a new search tool − an analysis form developed starting from the work of Gráinne Conole (2013) on MOOCs − used to analyze the level of inclusion of some university online  courses of the EduOpen platform. The aim of the work is to provide a self-analysis tool to better guide in an inclusive perspective those who design and deliver e-learning courses. The first results are encouraging and lead to further investment of resources in this direction.